The Jetted Tidal Disruption Event AT 2022cmc: Investigating Connections to the Optical Tidal Disruption Event Population and Spectral Subclasses through Late-time Follow-up - Hammerstein, Erica; Cenko, S. Bradley; Andreoni, Igor; Charalampopoulos, Panos; Chornock, Ryan; Margutti, Raffaella; O'connor, Brendan; Schulze, Steve; Sollerman, Jesper; Barway, Sudhanshu; Bhalerao, Varun; Anupama, G. C.; et al. (Institute of Physics Publishing, 2026)
AT 2022cmc is the first on-axis jetted tidal disruption event (TDE) to be discovered at optical wavelengths. The optically bright nature of AT 2022cmc presents an unprecedented opportunity to place this jetted TDE in the context of the larger optically selected thermal TDE population and explore potential connections to optical TDE subclasses, particularly the class of luminous TDEs that lack optical spectral features. In this work, we present late-time optical observations of AT 2022cmc, both imaging and spectroscopy, that extend the optical dataset to ∼160 days from the first detection in the observed frame. The light curve clearly evolves from red to blue, which we interpret as a transition from a nonthermally dominated spectral energy distribution (SED) to thermally dominated SED. By accounting for the nonthermal emission evident in the optical SED at early times, we extract the properties of the thermal emission and compare to a sample of optically selected thermal TDEs. We find that the properties of AT 2022cmc are consistent with previous correlations found for the evolution and properties of thermal TDEs, with the thermal properties of AT 2022cmc aligning with the class of featureless and luminous TDEs. The confirmation of this similarity motivates the importance of prompt and multiwavelength follow-up of featureless and luminous TDEs in order to further explore the connection they have with jetted TDEs.